The association between urinary antibiotics levels and the risk of adolescent depression - Yaling Jin; Xia Jin; Zhenhua Ge; Jianbiao Zhang; Yaqin Ding; Peijuan Wang; Jiancheng Qiu; Chao Liu; Zhenghui Yi; Ningwei Zhao; Ning Shen; Xuming Wu; et al. (Scientific Reports)
Abstract Antibiotics, through exposure via medication, food, and contaminated water, are recognized as risk factors for mental disorders in adolescents. This study aimed to evaluate the risks of antibiotic exposure in adolescents with depression. Sixty-two adolescents were divided into two groups based on their diagnoses: 32 in the healthy control group and 30 in the depression group. All urine samples were collected in the morning and subjected to urinary antibiotic analysis using liquid chromatography tandem mass spectrometry (HPLC-MS). Levels of four commonly used antibiotics—azithromycin, sulfadimidine, ofloxacin, and ampicillin—were measured in urine. The levels of all four antibiotics were significantly higher in the depression group and positively correlated with the HAMA score. Azithromycin (OR = 1.05, P = 0.002), sulfadimidine (OR = 1.22, P < 0.001), ofloxacin (OR = 3.79, P < 0.001), and ampicillin (OR = 352.57, P < 0.001) were risk factors for depression in adolescents. The ROC curve showed that the combination of all four urinary antibiotics exhibited the best performance in the prediction of the adolescent depression (AUC = 0.814, P < 0.001). Our study reveals antibiotic exposure is a modifiable risk factor for adolescent depression. Urinary antibiotic levels, particularly when combined, demonstrate potential as a screening tool for depression risk in adolescents.